Understanding academic performance of international students: The role of ethnicity, academic and social integration - Rienties, B.; Beausaert, S.; Grohnert, T.; Niemantsverdriet, S.; Kommers, Piet (Springer, 2012)
More than 3 million students study outside their home country, primarily at a Western university. A common belief among educators is that international students are insufficiently adjusted to higher education in their host country, both academically and socially. Furthermore, several groups of international students experience considerable amounts of stress while adapting to the culture of the host-institute. Several researchers argue that studies on adaptation of international students should widen its focus to the underlying mechanisms that leads towards this "misalignment". In a cross-institutional comparison among 958 students at five business schools in the Netherlands, differences in academic performance between local and international students were identified by focussing on their levels of academic and social integration. Students' academic integration was measured with the Students' Adaptation to College Questionnaire (SACQ), while students' social integration was measured with a newly developed and validated questionnaire. The results indicate that the degree of academic success of international students is multi-faceted. International students with a (mixed) western ethnic background perform well on both academic and social integration, and also attained higher study-performance in comparison to domestic students. In contrast, international students with a non-Western background are less integrated compared to other international students. Nevertheless, they have a similar study-performance. Finally, academic adjustment is the main predictor of study-performance for Dutch, Western and Mixed-Western students. Social adjustment was negatively related to study-performance. The lack of fit for predicting long-term study success of non-Western students indicates that their academic and social integration processes are more complex and non-linear.